Prevalence of leaf parasitism by insects and fungi in wild plant communities: implications for community assembly - Wang, Xi; Hiratsuka, Kazuyuki; Koike, Fumito (Frontiers in Ecology and Evolution, 2025)
IntroductionParasitism by infectious diseases and insect pests significantly shapes wild plant communities by stabilizing them through suppressing dominant species and destabilizing them by suppressing minor species. However, the dynamics of parasitism in wild ecosystems remain understudied. This study aimed to determine whether parasites infect a wide range of host species or are plant-specific, assess the stabilizing and destabilizing effects of parasitism on plant community structure, and determine the influence of environmental and seasonal factors on parasitism.MethodsWe conducted field surveys in herbaceous plant communities within a 1 km² area in the Tokyo metropolitan region, focusing on fungal diseases (rust-like and powdery mildew-like symptoms) and leaf-eating insect pests. Using zero-inflated binomial regression, we evaluated the symptom prevalence and intensity of parasitism across species, seasons, and environmental variables.ResultsThe results indicated that a few plant species were highly susceptible to parasitism, with rust-like infections tending to predominantly affect dominant species and leaf-eating insects targeting minor species.ConclusionThese findings highlight the contrasting roles of parasites in stabilizing and destabilizing plant communities and that both environmental and seasonal factors influence parasitism similar to cultivated ecosystems.